Problems of false positive laboratory tests during qualification to the ”Program of severe plaque psoriasis treatment” on the basis of two cases - Jaśkiewicz-Nyckowska, Dorota; Szczerkowska-Dobosz, Aneta; Czubek, Maria; Purzycka-Bohdan, Dorota (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Qualification of patients for the therapeutic program of severe plaque psoriasis should be preceded by many tests. Abnormal test results require further evaluation and possibly implementation of treatment. False positive results lead to prolongation of the qualification process and may cause disqualification of the patient. Objective. To draw attention to qualification to a drug program. Case reports . A screening test for Lyme disease performed in a 45-year-old man, during qualification for biological treatment, was positive, but verification by Western blot showed a negative result. It caused significant prolongation of the qualification process. In a 26-year-old patient the QuantiFERON test gave a positive result. It was repeated in another laboratory and a negative result was established. Conclusions . False-positive results may result in disqualification from biological treatment. Exchange of experience between doctors is essential for improving inclusion criteria of patients for biological therapy.